Pharmacogenetics of tenofovir and emtricitabine penetration into cerebrospinal fluid - Eric H. Decloedt; Phumla Z. Sinxadi; Lubbe Wiesner; John A. Joska; David W. Haas; Gary Maartens (AOSIS, 2021)
Background: Blood-cerebrospinal fluid (CSF) barrier transporters affect the influx and efflux of drugs. The antiretrovirals tenofovir and emtricitabine may be substrates of blood-brain barrier (BBB) and blood-CSF barrier transporters, but data are limited regarding the pharmacogenetics and pharmacokinetics of their central nervous system (CNS) penetration. Objectives: We investigated genetic polymorphisms associated with CSF disposition of tenofovir and emtricitabine. Method: We collected paired plasma and CSF samples from 47 HIV-positive black South African adults who were virologically suppressed on efavirenz, tenofovir and emtricitabine. We considered 1846 single-nucleotide polymorphisms from seven relevant transporter genes (ABCC5, ABCG2, ABCB1, SLCO2B1, SCLO1A2, SLCO1B1 and ABCC4) and 782 met a linkage disequilibrium (LD)-pruning threshold. Results: The geometric mean (95% confidence interval [CI]) values for tenofovir and emtricitabine CSF-to-plasma concentration ratios were 0.023 (0.021-0.026) and 0.528 (0.460-0.605), respectively. In linear regression models, the lowest p-value for association with the tenofovir CSF-to-plasma ratio was ABCB1 rs1989830 (p = 1.2 × 10−3) and for emtricitabine, it was ABCC5 rs11921035 (p = 1.4 × 10−3). None withstood correction for multiple testing. Conclusion: No genetic polymorphisms were associated with plasma, CSF concentrations or CSF-to-plasma ratios for either tenofovir or emtricitabine.